2019
DOI: 10.1111/jfpp.14066
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic esterification of rice bran oil and phytosterol in supercritical CO 2

Abstract: In this paper, the esterification of phytosterol and free fatty acids (FFA) in rice bran oil (RBO) was studied using Novozym 435 in supercritical CO2. It was found that with the increase in CO2 filling pressure, the esterification reaction rate also increased. When the pressure exceeded the critical point, CO2 fluid had a great effect on phytosterol conversion. Therefore, enzymatic esterification deacidification was studied when the CO2 filling pressure was 8.0 MPa, the results showed that when the lipase dosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…C. rugosa lipases are commercially available, usually as a mixture of isoenzymes, and are among of the most frequently used enzymes in biotransformations [138]. Lipase B from Candida antarctica (CALB), the most used commercial lipase, is also identified in Table 2 in a work performed by Yu et al [76] in 2019, with high conversion values (93.2%). Additionally, He et al [65] compared this enzyme with C. rugosa lipase for the transesterification of phytosterols with ethyl linolenate and obtained a conversion four times lower than for CALB.…”
Section: General Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…C. rugosa lipases are commercially available, usually as a mixture of isoenzymes, and are among of the most frequently used enzymes in biotransformations [138]. Lipase B from Candida antarctica (CALB), the most used commercial lipase, is also identified in Table 2 in a work performed by Yu et al [76] in 2019, with high conversion values (93.2%). Additionally, He et al [65] compared this enzyme with C. rugosa lipase for the transesterification of phytosterols with ethyl linolenate and obtained a conversion four times lower than for CALB.…”
Section: General Aspectsmentioning
confidence: 99%
“…There are still a few studies using supercritical fluids for the synthesis of phytosterol esters. YU et al [76] studied the esterification of phytosterol and free fatty acids using Novozyme 435 in supercritical CO 2 and found that with increasing CO 2 filling pressure, the esterification reaction rate also increased, obtaining an esterification yield of 93.2%.…”
Section: Potential Technologies For Biocatalytic Synthesis Of Phytosterol Estersmentioning
confidence: 99%
See 1 more Smart Citation
“…This proved the existence of a synergistic effect between bimetallic catalysts (Mironenko et al, 2018). Yu et al (2019) performed an enzymatic esterification reaction in supercritical CO 2 , which shortened the esterification time and made the conversion rate of plant sterols reach 93.2%. Yu et al (2017) performed a hydrogenation reaction in supercritical CO 2 , and the reaction time was reduced by 4 h.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al . (2019) performed an enzymatic esterification reaction in supercritical CO 2 , which shortened the esterification time and made the conversion rate of plant sterols reach 93.2%. Yu et al .…”
Section: Introductionmentioning
confidence: 99%